Da dúvida nasceu uma certeza: Ser Professora - Ana Francisca Costa e Sousa (2021)
The purpose of this report is to analyze the pedagogical internship process, from the 2020/2021 school year, as part of the Master's Degree in Physical Education Teaching in Basic and Secondary Education. The internship was developed at Escola Secundária de Rio Tinto, which is part of the Rio Tinto Schools Group. This report will describe the activities developed during the internship process, highlighting the difficulties experienced, namely those arising from the situation caused by the COVID-19 pandemic, which had strong effects on the strategies used, on the evaluation and on the various relationships with all actors involved in the process. It was an atypical year that gave rise to the need for permanent adaptation due to the limitations and confinement rules that were imposed at the school. The report presents a "case study" on the perception of the impact of the "Covid 19" pandemic among students of the 10thG Science and Technology class at Rio Tinto Secondary School. The research is limited to a space and a time, that is, it is unique, as it is not intended to represent the world, but to represent the case. It aims to provide a global perspective, as congruent and integral as possible, of the object under study. In this sense, it is not intended to generalize the research findings, but rather that this study can be another look at the problem of the impact of the covid 19 pandemic in the school reality, namely in the subject of Physical Education, in order to contribute to a better knowledge of the reality that is currently lived in schools. This report intends to be a reflection more than factual about the internship, intending to be projective in the sense of outlining guidelines for my future profession as a Physical Education teacher. The internship process proved to be essential to acquire new knowledge, skills and methods, always with the aim of promoting the development of Physical Education in student's learning.